Images of scales : an English-Slovenian contrastive analysis of idiomatic minimizers and maximizers - Ilc, Gašper (Array, 2019)
The paper investigates the syntactic, semantic, and cultural properties of minimizers and maximizers from a contrastive perspective. Minimizers and maximizers are scalar constructions whose function is to strengthen the speaker’s (negative) assertion by pointing to the minimal (minimizers) or the maximal (maximizers) point on a pragmatic scale. The syntactic analysis reveals that these items are predominantly sub-clausal (V+NP/PP or NP/PP), and polarity sensitive, requiring the presence of a polarity licenser. The lexical analysis identifies three possibilities with regard to lexical selections in the two languages: a complete, partial, and a non-existent lexico-semantic overlap. Furthermore, the corpus data indicate that there is considerable variation in the lexical items appearing in minimizers and maximizers (e.g., give a damn/shit/toss/fuck/monkey’s/fig/rat’s (arse, ass, fart)/hoot). Even though minimizers and maximizers in both languages involve the metaphor more is up, less is down / good is up, bad is down and part-for-whole metonymy, the analysis shows that the lexical selection in the two languages diverges due to different cultural conceptualisations and cultural background. The observation and results of the analysis presented herein aim at contributing to a better understanding of idiomatic expressions from the viewpoint of contrastive linguistics, cultural studies, and cultural conceptualisation.